The effectiveness of tilawati, ummi, and talaqqi methods on BTQ learning outcomes regarding the gender of elementary students in Bandung - Hafilda Anisa; Rindang Rabi’ah Adawiyah; Ariibah Radita Ayu Candrika; Sal Shakhiba Albira Nanda Hanafi; Zulfa Uswatun Hasanah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to compare students’ learning outcomes in reading and writing the Qur’an (BTQ) based on three teaching methods: Tilawati, Ummi, and Talaqqi. While taking gender differences into account. This study employs a quantitative comparative approach involving 87 elementary school students from three Islamic schools in Bandung. Data were analyzed using SPSS 25, with assumptions tested, and two-way ANOVA, the Median Test, and the Mann-Whitney U Test used as post hoc analyses. The results indicate significant differences in BTQ learning outcomes among the three teaching methods. Post hoc analysis reveals significant differences between the Tilawati and Ummi methods (p = 0.001), the Tilawati and Talaqqi methods (p = 0.010), and the Ummi and Talaqqi methods (p < 0.000). Among the three methods, the Ummi method yielded the highest learning outcomes. Furthermore, no significant differences in BTQ learning outcomes were found by gender (p > 0.05). Interaction analysis also indicates that gender did not significantly moderate the relationship between learning methods and BTQ learning outcomes (p = 0.367), a finding further supported by profile plots showing relatively parallel patterns across all gender groups. The contribution of this study lies in the simultaneous comparison of three widely used BTQ learning methods within the same educational context while incorporating gender as an analytical variable. These findings suggest that the choice of learning method plays a more substantial role in determining BTQ learning outcomes than gender differences, with the Ummi method yielding the most favorable results in this study.